SAVI Approach Paper 9: Engaging State Houses of Assembly - SAVI (DFID, 2015)
The overall aim of SAVI engagement with SHoAs is to promote lasting re forms that are not dependent on external funding and which promote an increasingly more responsive and accountable relationship between Nige rian state governments and their citizens. SHoAs are supported to be m ore effective agents of citizen voice and public accountability, deman ding better performance from...